Food Security Policy Analysis through a Multisectoral Approach to Achieve Sustainable Food Security in Central Sulawesi - Ade Putra Ode Amanne; Filo Leonardo Tinggogoy; Srifridayanti Srifridayanti; La Ode Sabirila Jayalangi; Fadli Sandewa (Department of Public Administration, 2026)
This study analyzes food security policy in Central Sulawesi through a multisectoral approach aimed at achieving sustainable food security. The research employs a qualitative method with a case study design, integrating primary data obtained through in-depth interviews with key institutional actors and an analysis of regional policy documents. The findings indicate that although Central Sulawesi possesses abundant natural resources and records a rice surplus, disparities in food access persist, as reflected in the increasing number of priority food-insecure subdistricts. The regional government has undertaken various initiatives to strengthen food security, including innovative programs such as Tetra Pandu, the Gerakan Pangan Murah (Affordable Food Movement), and local food diversification involving cross-sectoral collaboration. However, policy implementation continues to face significant challenges, including weak inter-agency coordination, the absence of integrated cross-sectoral data systems, limited logistics infrastructure, commodity price volatility, and vulnerability to natural disasters. From a theoretical perspective, this study contributes to the literature on network governance in regional public policy by highlighting the limitations of hierarchical administrative models in the context of multisectoral food policy. Practically, the study recommends strengthening cross-sectoral data integration, institutionalizing horizontal coordination mechanisms, and reforming governance architecture to promote a more sustainable and adaptive regional food security system.